Social enterprises and sustainability in Gauteng, South Africa - Bungu, Johnson Bungu (University of the Free State, 2023)
Social entrepreneurship has become essential in several developed and underdeveloped countries (Defourny and Nyssens, 2010). In 1980, social entrepreneur Bill Drayton founded the Ashoka Innovators for the Public organisation (Shapiro, 2010). Ashoka referred to a passionate entrepreneur who was tackling a social issue. The entrepreneur’s objective would be a social mission that is backed by entrepreneurial qualities of dynamism, innovation, and dedication. According to Shapiro (2010), the term has evolved and now has different meanings. Some of these include social activities with business attributes and businesses themselves. It is a business; however, it has a social objective, and any surplus income is invested (Roy et al., 2010). Social entrepreneurship creates value instead of capturing value (Santos, 2012). According to Littlewood (2015), the social mission is the most critical objective. Profits are the route to achieve this objective and are reinvested in the organisation and not given out to shareholders. It is an emerging field with no consensus on the definition (Austin et al., 2006). In Europe, the conversations and ideas of social entrepreneurship began in the 1990s, while in the United States, the Harvard Business School started an initiative on social entrepreneurship in 1993. There were, however, different understandings and no consensus on what social entrepreneurship was (Bennati and Radi, 2018). Various institutions were set up, with universities starting research and training programmes in this area. Other networks were set up, including the emergence of social enterprises in Europe, such as the EMES European Research Network and the Social Enterprise Knowledge Network for Latin American business schools. This further led to various European countries passing laws that promoted social entrepreneurship. The European approach to social entrepreneurship emphasised the collective, cooperative and associative forms. Social entrepreneurship is also attracting attention in Latin America and Eastern Asia (Defourny and Nyssens, 2010). Here, social networks are essential for understanding social entrepreneurship for three reasons: They drive the flow and quality of information and determine rewards and punishments. Trust emerges through social networks, which impact the cost of transactions. Social networks, therefore, influence the organisation’s performance and access to resources and help build legitimacy; social entrepreneurship results from pooling and exchanging resources by different organisations. Social entrepreneurs rely on wide and personal networks, unlike commercial businesses, which depend on professional networks (Trivedi and Stokols, 2011). When social entrepreneurs address social problems, this creates social value. High unemployment, poverty and inequality are experienced in South Africa. These have remained extremely high and are predicted to remain as economic growth prospects are bleak. Social entrepreneurship, among other solutions, may help to address this situation. However, social entrepreneurship has faced sustainability challenges, and it is essential to look at how some established social enterprises have sustained themselves. This may help develop the sector in the Gauteng as well as the rest of the country.
Dissertation(MDS (Development Studies))--University of the Free State, 2023
Keywords: Social entrepreneurship; Ashoka Innovators for the Public organisation; EMES European Research Network; Social Enterprise Knowledge Network for Latin American business schools; Gauteng